Hubungan Work Engagement dan Readiness for Change Guru SMP Negeri di Bandung - Awang Lukman Nur Karim; Hendro Prakoso (Bandung Conference Series: Psychology Science, 2024)
Abstract. At this time, change is inevitable in the sustainability of a company or organization. This includes changes that occur in the field of education, namely the Independent Curriculum. In the face of change, teachers need to have high readiness for change. Readiness For Change is defined as the readiness of individuals to face changes that occur in the organization. Readiness For Change is a multidimensional construct correlated by beliefs among employees Holt et al (2007). Readiness for change can be improved through work engagement. Work engagement is defined as a positive and satisfying work-related state of mind characterized by vigor, dedication, and absorption (Schaufeli &; Bakker, 2010). This study aims to determine how closely the relationship between work engagement and readiness for change. This research was conducted on public junior high school teachers in the city of Bandung who were conducting the Independent Curriculum. The sample in this study amounted to 97 public junior high school teachers in the city of Bandung. The measuring instrument used in the readiness for change variable comes from Holt (2007) adapted by Wisnu et al (2022). This measuring instrument has 25 items. Meanwhile, work engagement is measured using Utrecht Work Engagement Scale-17 (UWES-17) from Schaufeli & Bakker adapted by Angga et al (2020). The data analysis used is a product moment test. The results of the study found that readiness for change has a strong relationship with work engagement by 90% with the aspect that has the greatest relationship, namely appropriatness to work engagement in participants of public junior high school teachers this study. Abstrak. Pada saat ini, perubahan merupakan hal yang tidak dapat dihindari dalam keberlangsungan suatu perusahaan atau organisasi. Hal ini termasuk perubahan yang terjadi dalam bidang pendidikan yaitu Kurikulum Merdeka. Dalam menghadapi perubahan, guru perlu memiliki readiness for change yang tinggi. Readiness For Change didefinisikan sebagai kesiapan individu dalam menghadapi perubahan yang terjadi pada organisasi. Readiness For Change adalah konstruksi multidimensi yang dikorelasi oleh keyakinan di antara karyawan Holt et al (2007). Readiness for change dapat ditingkatkan melalui work engagement. Work Engagement didefinisikan sebagai sebagai keadaan pikiran yang berhubungan dengan pekerjaan yang positif dan memuaskan yang ditandai dengan vigor, dedication, dan absorption (Schaufeli & Bakker, 2010). Penelitian ini bertujuan untuk mengetahui seberapa erat hubungan antara work engagement dan readiness for change. Penelitian ini dilakukan kepada guru smp negeri di kota Bandung yang sedang melakukan Kurikulum Merdeka. Sampel pada penelitian ini berjumlah 97 guru smp negeri di kota Bandung. Alat ukur yang digunakan pada variabel readiness for change berasal dari Holt (2007) yang diadaptasi oleh Wisnu et al (2022). Alat ukur ini memiliki 25 item. Sedangkan untuk work engagement diukur menggunakan Utrecht Work Engagement Scale-17 (UWES-17) dari Schaufeli & Bakker yang diadaptasi oleh Angga et al (2020). Analisis data yang digunakan adalah uji product moment. Hasil penelitian ditemukan bahwa readiness for change memiliki hubungan yang kuat terhadap work engagement sebesar 90% dengan aspek yang memiliki hubungan paling besar yaitu appropriatness terhadap work engagement pada partisipan guru smp negeri penelitian ini.